Emotional, Physical and Sexual Abuse Impact in Children and Social Minorities - Corona, Giovanni; Jannini, Emmanuele A.; Maggi, Mario (Springer International Publishing : Imprint: Springer, 2014)
This book describes different kinds of psychological, physical and sexual maltreatment and explains their possible consequences, especially as regards quality of life, psychopathology and sexual life. The focus is specifically on the victims of abuse, who are among the more frail and vulnerable members of society. The book examines the impacts of maltreatment of both children and social minorities, such as homosexuals and gender dysphoric individuals or those affected by disabilities and describes skills that are of value in supporting victims of maltreatment and preventing discrimination. The work will be useful to sexual medicine specialists, medical doctors, psychologists and psychiatrists, as well as graduate students in these disciplines. By fostering a better understanding of discrimination triggers and effects, it will help clinicians to provide improved support through the tailoring of therapies to the needs of maltreated individuals.